2003
DOI: 10.1046/j.1365-2036.2003.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of factors influencing short‐term and sustained response to infliximab treatment for Crohn's disease

Abstract: Summary Background: 59–81% of patients given infliximab for Crohn's disease will respond. Although now in widespread use, little consensus exists regarding the optimal place in patient care. Recently developed guidelines have identified need for markers that predict response. Aims: We aimed to identify markers of response to infliximab given for Crohn's disease. Methods: Markers of response (defined at 4 weeks) were prospectively assessed in 74 infliximab‐treated patients with Crohn's disease. Patients were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 31 publications
4
104
2
7
Order By: Relevance
“…Early reports of anti-TNF therapy found that 22% of smokers vs. 74% of nonsmokers responded to episodic use of infl iximab ( 175 ), and a prospective study of 74 patients given a single dose of infl iximab found that at 4 weeks smokers were less likely to have a response (OR 0.22; 95% CI, 0.08-0.41) and a shorter duration of response than non-smokers ( 176 ). In a retrospective study, patients with CD who continued to smoke required new courses of steroids and in multivariate analysis, smoking status was the only predictive factor of drug tolerance ( 177 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Early reports of anti-TNF therapy found that 22% of smokers vs. 74% of nonsmokers responded to episodic use of infl iximab ( 175 ), and a prospective study of 74 patients given a single dose of infl iximab found that at 4 weeks smokers were less likely to have a response (OR 0.22; 95% CI, 0.08-0.41) and a shorter duration of response than non-smokers ( 176 ). In a retrospective study, patients with CD who continued to smoke required new courses of steroids and in multivariate analysis, smoking status was the only predictive factor of drug tolerance ( 177 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Established predictors of relapse of disease activity in CD such as smoking and use of non-steroidal anti-inflammatory drugs (NSAID), 24 as well as the predictors of short-and long-term response to infliximab such as concomitant use of immunosuppressive therapy, age and location of disease were recorded. [25][26][27][28] The phenotype of the CD patients was described using the Vienna classification. 29 Age at diagnosis, disease duration, surgical history, time since previous treatment for a flare and the number of treatments for CD during the previous 12 months were recorded as well.…”
Section: Measurement Of Disease-related Characteristicsmentioning
confidence: 99%
“…1 Administration of recombinant immunomodulatory cytokines or monoclonal antibodies to neutralize specific inflammatory mediators has been shown to be effective in various inflammatory disorders. 2,3 Although cytokine-based therapy may represent an attractive therapeutic option for patients unresponsive to traditional treatments, systemic administration of such molecules has several drawbacks: short bioactivity, systemic toxicity, and high cost. 1 Administration of genes coding for immunomodulatory cytokines, aimed at providing therapeutic levels of cytokines produced directly in patient's tissues, gave exciting results in several models of immune-mediated diseases.…”
Section: Introductionmentioning
confidence: 99%